Improving Teachers ’Skills Through Simple Instructional Media Development Training - Hidayat, Nur; Rizqi Salamah, Evi (Kontribusia : Research Dissemination for Community Development, 2020)
This training activity aimed to provide understanding & application of simple media to teachers at Kuncup Melati Sooko Kindergarten, Mojokerto. The subjects of this training were the early childhood teachers of Kuncup Melati Sooko Kindergarten. In implementing this training, the researcher used demonstration, practice, and discussion. These training results indicated that it increased the teachers’ ability to develop simple media and their application in learning at the early childhood education level.